Electro Cardiogram and Its Normal Variations in Healthy Adults (Academia Journal of Medicine, 2019)
Background: Electro cardiogram is used to assess cardiac, rhythm and conduction and provides information about chamber size also. The  Electrical activity is initiated in SA node and then to AV node and then to bundle of HIS and from that through the purkhji system spread to  myocardium. Electrocardiogram is the best non-invasive investigation in diagnosing acute myocardial infarction and arrhythmias like atrial  fibrillation and ventricular tachycardia. Electrolyte abnormalities like hypokalaemia and hyperkalaemia may also be detected with  electrocardiogram. Aim: To study the normal variations QRS duration, ST, T changes and other rate and rhythm abnormalities, which can  occur in healthy individuals. Subjects and Methods: We have examined 280 healthy adults , among those 280 ,120 were females and 160  were males. The age group is between 20 and 60 years. ECG’S were taken after Careful history and clinical examination to rule out any heart  diseases like coronary heart diseases, rheumatic heart diseases and hypertensive heart diseases. Drug history was also recorded especially  regarding B blockers and Calcium channel Blockers. Results: Out of 280, females were 120 and males were 160 the age group is between 20  and 60 years. The heart rate is between 56 and 104. Normal sinus rhythm is observed in 146. The increased heart rate is seen in young adults  ,T↓ are very common. Conclusion: Electro cardiogram is a best investigation in diagnosing acute myocardial infarction and certain  arrhythmias. Even though normal variations are common it is very much useful in detecting certain conditions like silent Myocardial infarction  which is very common in diabetic patients and old age Individuals.
Keywords: Electro cardiogram; Bradycardia; Tachycardia; P-R interval; T Wave inversion; Incomplete RBBB